Analysis of Turkish children's dental anxiety by various psychological tests - Demiröz, Işık (The Turkish Journal of Pediatrics, 1985)
The purpose of this investigation was to study anxiety of children vis-à-vis dental treatment in the dentist’s office and in the classroom. Various tests were applied to 75 children who ranged in age from 8 to 11 years. The children were evaluated in three groups: clinical, letter and school groups.The behavior of the children was rated by Frankl’s Behavior Pattern, and the anxiety of the children was rated by using the Goodenough “Draw a Man” test. The relationship between maternal anxiety and child behavior was also studied.The results of this study indicate that among the three groups the school group was the most anxious and the letter group the least. The boys were more anxious than the girls (p
Keywords: childhood behavior; dental anxiety; maternal anxiety; perceptual drawings; psychodynamic analysis